Evaluation of Gastritis Medication in Patient Prescriptions at the Inpatient Ward of Labuang Baji Regional General Hospital in Makassar City - Rizky Indah Pratiwi; Muhammad Yusuf; Ummu Kalsum Tamsil (MASHIJO : Medical Science and Hospital Journal, 2023)
Background: Gastritis is an inflammation of the gastric mucosa caused by various factors, such as dietary patterns, lifestyle, irritation, and infection. The disease occurs due to inflammation in the gastric lining, leading to abdominal pain. The purpose of this study was to determine the use and suitability of ranitidine medication in gastritis patients admitted to the inpatient ward of RSUD Labuan Baji in Makassar City. Method: This research employed a descriptive design with a cross-sectional approach. The sample consisted of inpatients from the period of 2018-2020. The data collected were secondary data obtained by the researchers from medical records and the pharmacy department regarding inpatient gastritis patients. Result: The drug interaction identification indicated that the highest percentage of interactions was related to pharmacokinetic mechanisms, specifically absorption, accounting for 85.7% when the effect was reduced. The lowest percentage of interactions, at 14.3%, was related to pharmacodynamic interactions that exhibited a synergistic effect when intensified. Conclusion: Gastritis is a prevalent disease in Indonesia with an increasing number of patients each year. It is crucial to take gastritis seriously as it can impair gastric function and elevate the risk of fatal stomach cancer. Additionally, drug interactions should be considered due to their potential harmful or beneficial consequences.